(untitled) (Research, Society and Development, 2022)
Objective: To know the aspects related to the incidence of meningitis in Paraná between the years 2010 and 2020 and to evaluate the sociodemographic profile of the affected population. Methods: This is an epidemiological and authorized study that used data from the Diseases and Notification System. Results: Male individuals, aged between 0 to 4 years and 20 to 39 years and of white ethnicity, are the most affected. Viral meningitis were the most prevalent, followed by bacterial meningitis, and among meningitis, those chosen by serogroup C stood out. Most patients were discharged and mortality in the period evaluated was 6.6%. Conclusions: It is concluded that the findings of this work are in line with other national studies demonstrating that there is an epidemiological trend in the course of meningitis in Brazil.